Pengenalan dan Penggunaan Website Ujian Online Sebagai Media Pembelajaran Pada Siswa/Siswi SMA Negeri 1 STM Hilir - Soeb Aripin; Natalia Silalahi; Kurnia Ulfa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The introduction and use of this Online Website for learning activities is aimed at making high school students able to learn easily by utilizing technology. In the introduction and use of the Online Exam Website, we will introduce and use the Online Exam Website, one of which is through the website